Principal's Strategic Planning in Improving the Quality of Education in Bontang City Vocational High Schools - Anugrah Anugrah; Zaenab Hanim; Nurlaelah Nurlaelah (PT ARRUS Intelektual Indonesia, 2022)
This study aims to describe the principal's strategic planning in improving the quality of education at Bontang City Vocational High School. This study uses a qualitative approach, it is based on the intention to describe the behavior of informants, namely implementing educational planning in improving the quality of education. Data collection methods used are observation, interviews, and documentation. Primary data sources in this study were directed at finding data from school principals, vice principals, and teachers. The search for data started with the principal as a key informant by using snowball sampling. then the teachers who manage student learning. The adequacy of the data is based on the saturation of the data, that is if the data from one data and the other data are the same. Secondary data sources are carried out by processing information obtained from the field in the form of notes and documents related to the research focus. Data analysis in this study took place simultaneously with the data collection process, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the principal's strategic planning in improving the quality of education in Bontang City Vocational High Schools are: (1) Implementation of programs relevant to planning for improving the quality of education; (2) School principals prioritize cooperation and maintain stability and sustainability of education quality improvement policies; (3) Managing school and community relations to implement education quality improvement plans; (4) manage teachers and staff to synergize in the planning and implementation of quality improvement, and are highly committed to planning for improving the quality of education in their schools.